Pengelolaan Administrasi Di Madrasah Ibtidaiyah Al-Fattah Kota Malang - Wafa Hududallah I.A. (Leadership: Jurnal Mahasiswa Manajemen Pendidikan Islam, 2021)
This study wants to explore administrative management at Madrasah Ibtidaiyah Al-Fattah Malang. This research is a qualitative research. Data collection uses the method of documentation and unstructured interviews. The result is that the administrative management at MI Al-Fattah is generally quite good, but there is still a lot that needs to be addressed to achieve an ideal administrative order, starting with the management of student office personnel administration, and the infrastructure has been managed quite well. Al-fattah is a wholehearted service shown by the friendliness of all educators and education staff in serving students and guardians of students. It is necessary to optimize and digitize the overall administrative management to make it easier to access